KESADARAN DAN KETERLIBATAN UMAT DALAM HIDUP MENGGEREJA DI STASI ST. THERESIA KM.26 PATAS I - Marselus Kristian Prinando; Silvester Adinuhgra; Paulina Maria. E.W; Widya Ariyani (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2021)
This study aims to describe the awareness and involvement of the people in church life at Santa Theresia Km.26 Patas 1 station. This research was based on phenomena or what happened in the field, that awareness and involvement of people in church activities is still not actively involved. This type of research is descriptive qualitative. Data obtained by using interviews and documentation. The research was conducted in June at Santa Theresia Km.26 Patas 1 station. There were 8 informants in this study consisting of parish priests, community leaders, and people at Santa Theresia Km.26 Patas 1 station. Data analysis techniques used the Miles and Miles model. Huberman which consists of 3 stages, namely reduction, data presentation, and drawing conclusions.